Possession of the educational competencies of the teaching staff at the Brack College of Education from their prospective (Journal of Human Sciences, 2021)
This study aimed to identify the degree to which faculty members at the brack college of education possess educational competencies from their point of view based on  the following variables : academic degree, years of experience and academic qualification. The study sample consisted of (31) faculty members.  The study tool is a questionnaire  that consisted of (27)  varied  adequacies.  The results showed that the faculty members’ possession of educational competencies came to a high degree with a percentage of (83.35), and the results showed that there were no statistically significant differences according to the variables of academic degree, years of experience and academic qualification. The study  was concluded with some   recommendations and suggestions.